Sign language courseware / Hazimah Mohd Isa - Mohd Isa, Hazimah (2012)
Teaching sign language nowadays with the traditional approach is not interesting. Students only are showed with the information wrote in the text book or blackboard and do a manual assessment to understand the content of learning. Now, in the rapid development of information and communication technology (ICT) era, there are many computer-based learning that exists. With the help of computer-based learning, it will simplify teaching, learning process and give an alternative for teachers to express or teach the information and education for students. Therefore, the objectives of this project are to design a courseware to teach sign language for children, to develop a courseware on teaching sign language and to test the functionality of the courseware. The courseware was built using Adobe Flash 8 and Adobe Photoshop. After completion of this courseware, Sign Language Courseware was evaluated by10 people who are the student of sciences computer in FSKM. Parents showed satisfaction on the performance of their children and the courseware capabilities. There commended future work is by adding more learning videos so that everyone can learn and gain more knowledge about the other sign language since this courseware only provided basic sign language. In addition, the games can be improved by enhance it to video instead of using picture or image.